Coupling Lipid Labeling and Click Chemistry Enables Isolation of Extracellular Vesicles for Noninvasive Detection of Oncogenic Gene Alterations. Issue 14 (9th March 2022) - Sun, Na; Tran, Benjamin V.; Peng, Zishan; Wang, Jing; Zhang, Ceng; Yang, Peng; Zhang, Tiffany X.; Widjaja, Josephine; Zhang, Ryan Y.; Xia, Wenxi; Keir, Alexandra; She, Jia‐Wei; et al.
Abstract: Well‐preserved molecular cargo in circulating extracellular vesicles (EVs) offers an ideal material for detecting oncogenic gene alterations in cancer patients, providing a noninvasive diagnostic solution for detection of disease status and monitoring treatment response. Therefore, technologies that conveniently isolate EVs with sufficient efficiency are desperately needed. Here, a lipid labeling and click chemistry‐based EV capture platform ("Click Beads"), which is ideal for EV message ribonucleic acid (mRNA) assays due to its efficient, convenient, and rapid purification of EVs, enabling downstream molecular quantification using reverse transcription digital polymerase chain reaction (RT‐dPCR) is described and demonstrated. Ewing sarcoma protein (EWS) gene rearrangements and kirsten rat sarcoma viral oncogene homolog (KRAS) gene mutation status are detected and quantified using EVs isolated by Click Beads and matched with those identified in biopsy specimens from Ewing sarcoma or pancreatic cancer patients. Moreover, the quantification of gene alterations can be used for monitoring treatment responses and disease progression. Abstract : This work demonstrates an efficient and rapid extracellular vesicle (EV) capture platform ("Click Beads"), which enables downstream quantification of gene alterations in both Ewing sarcoma and pancreatic cancer using reverse transcription digital polymerase chain reaction (RT‐dPCR). The streamlined workflow that combines Click Bead‐based EV capture and RT‐dPCR exhibits potential clinical utility in disease detection and treatment response monitoring.